Analysis of Regional Tax Management Based On Information System Management of Regional Original Revenue (SIP-PAD) at The Agency Kendari City Regional Revenue (BAPENDA) - Andi Basru Wawo; Tasya Rahmadini; Muh. Nur; Bucek Jalu Prasetyo Arjuna (PT. Publikasiku Academic Solution, 2024)
This research aims to find out and analyze how regional tax management is based on the Regional Original Income Management Information System (SIP-PAD) at the Kendari City Regional Revenue Agency and the extent to which regional tax management is based on the Regional Original Income Management Information System (SIP-PAD) at the Revenue Agency Kendari City area. This research uses qualitative methods with the data used coming from primary data in the form of interviews and secondary data in the form of documentation. The results of this research show that SIP-PAD based Regional Tax Management at BAPENDA Kendari City has been implemented in accordance with existing policies, namely PP No. 35 Article 59 of 2023 where Regional Governments are required to make Payments and Deposits via an electronic-based system. Which refers to the previous statement, namely Minister of Home Affairs Regulation Number 56 of 2021 concerning Teams for the Acceleration and Expansion of Digitalization in Provincial and Regency/City Regions as well as procedures for Implementing Regional Government Transaction Etronification (E-STPD). This is because the integrated and computerized system allows tighter monitoring of potential tax fraud and abuse.